Prevalence and sociodemographic correlates of meeting the Canadian 24-hour movement guidelines among latin american adults: a multi-national cross-sectional study - Ferrari, Gerson (2022)
Background: 24-hour movement behaviors, including moderate-to-vigorous physical activity (MVPA), sedentary time (ST), and sleep duration, have important implications for health across the lifespan. However, no studies exist that have examined the integration of these 24-hour movement behaviors in Latin America. The purpose of this study was to examine the prevalence of meeting the Canadian 24-Hour Movement Guideline recommendations and sociodemographic correlates of meeting the guidelines in adults from eight Latin American countries. Methods: This was a multi-national cross-sectional study of 2338 adults aged 18 to 64 years from the Latin American Study of Nutrition and Health. MVPA and ST data were collected using accelerometers. Sleep duration was self-reported using a daily log. Socio-demographic correlates included sex, age, education level, and marital status. Meeting the 24-hour movement guidelines was defined as: ≥150 min/week of MVPA; ≤8 h/day of ST; and between 7 and 9 h/day of sleep. Logistic regression models were estimated on pooled data. Results: The prevalence of adults who met the MVPA, ST, sleep duration, and integrated recommendations was 48.3, 22.0, 19.4, and 1.6%, respectively. Overall, being a woman (OR: 0.72; 95%CI: 0.55,0.93) and having a middle (0.63; 0.47,0.85) or high education level (0.31; 0.17,0.56) was associated with lower odds of meeting all three of the 24-hour movement guideline recommendations. Being married (1.70; 1.25,2.29) was associated with greater odds of meeting all three recommendations. Being a woman (0.46; 0.39,0.55), aged 50-64 years (0.77; 0.60,0.97), and married (0.79; 0.65,0.96) were associated with lower odds of meeting the MVPA recommendation. Having a middle (0.64; 0.50,0.80) or high (0.36; 0.23,0.55) education level was associated with lower odds and being married (1.86; 1.46,2.36) was associated with greater odds of meeting the ST recommendation. Being a woman (0.63; 0.51,0.78) was associated with lower odds; whereas being aged 50-64 years (1.40; 1.04,1.88) and having a middle education level (1.37; 1.09,1.73) were associated with greater odds of meeting the sleep duration recommendation. Conclusions: Overall, the proportion of Latin American adults achieving healthy levels of 24-hour movement behaviors was low. Further efforts are needed to promote more MVPA, less ST, and sufficient sleep in Latin American adults. Trial registration: Clinical Trials NCT02226627. Retrospectively registered on August 27, 2014.